2019
DOI: 10.1128/aac.00054-19
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Screen Reveals a Diverse Collection of Medications That Induce Antifungal Resistance in Candida Species

Abstract: The increasing incidence of and high mortality rates associated with invasive fungal infections (IFIs) impose an enormous clinical, social, and economic burden on humankind. In addition to microbiological resistance to existing antifungal drugs, the large number of unexplained treatment failures is a serious concern. Due to the extremely limited therapeutic options available, it is critical to identify and understand the various causes of treatment failure if patient outcomes are to improve. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…CDR2 encodes a multi-drug efflux pump of the ATP-binding cassette superfamily and has an established role in facilitating genetically encoded azole resistance in C. albicans (26), while RTA3 encodes a phospholipid translocase also previously shown to affect azole-tolerance (27). These results are consistent with our previous data showing that the azole-antagonistic activity of aripiprazole is dependent upon the Tac1p transcription factor, which activates the transcription of CDR2 (16). Several additional transcripts known to be either induced by Tac1p, or following exposure to fluphenazine (a known activator of Tac1p) (28), were identified as being elevated by one or more of the three drugs.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…CDR2 encodes a multi-drug efflux pump of the ATP-binding cassette superfamily and has an established role in facilitating genetically encoded azole resistance in C. albicans (26), while RTA3 encodes a phospholipid translocase also previously shown to affect azole-tolerance (27). These results are consistent with our previous data showing that the azole-antagonistic activity of aripiprazole is dependent upon the Tac1p transcription factor, which activates the transcription of CDR2 (16). Several additional transcripts known to be either induced by Tac1p, or following exposure to fluphenazine (a known activator of Tac1p) (28), were identified as being elevated by one or more of the three drugs.…”
Section: Resultssupporting
confidence: 93%
“…This specific study assessed the impact of several drugs we previously found to oppose the antifungal activity of the azole class of antifungals, upon C. albicans (16). Genetically encoded azole-resistance in C. albicans is often associated with point mutations in one or more key transcription factors that regulate the expression of the target enzyme Erg11p, or of multi-drug efflux pumps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Invasive fungal infections produced by Candida spp. persist as the primary hospital-acquired bloodstream infections and are associated with high morbidity and mortality, especially in intensive care units (Kauffman, 2015;McCarthy and Walsh, 2017;Butts et al, 2019). While Candida albicans remains as the most frequent fungal species isolated from candidemic patients, other Candida species are often identified in clinical isolates (Reviewed in Guinea, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It also contains a pre-processed tabular data file (“Data06_Raw02_ButtsEtAl_Antifungal.txt”) containing the assay results for penbutolol and fluconazole in an antifungal screen reported by Butts et al. [9] . The R script file “Data06_Script01_AtypicalSurfaces.R” extracts the data from these two files, fits them with a traditional BRAID surface, as well as a transformed oppositional or protective BRAID surface, and reports all fit results.…”
Section: Data Descriptionmentioning
confidence: 99%